THE «ESIM-ZYLIKA» EPIC: MANUSCRIPT VERSIONS AND TEXTUAL FEATURES (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
Five handwritten versions of the epic ‘Esim-Zylika’ stored in the archives of the M. Auezov Institute of Literature and Art and the Central Scientific Library were used as the main material for the present research.The systematic study of epics about lovers took shape in Kazakh folklore studies in the second half of the 20th century. In this regard, this article analyses the works of M. Auezov, A. Konyratbayev, Y. Duisenbayev, B. Azibayeva and other well-known scholars. Based on the conclusions of these researchers, the authors of the article demonstrate the transitional nature and interconnection between authorial adaptation and folk traditions in the texts of love epics between folklore and written literature. Based on B. Azibayeva's classification, the division of love epics into three groups of social and love tales based on Eastern plots, regional folklore and specific historical events are considered as an important scientific direction for analyzing their artistic nature.Although the content of the epic ‘Esim-Zylika’ is typologically similar to classical Eastern tales, the work is considered to have absorbed the Kazakh worldview, national traditions and historical and social realities. The study proves that the 1923 version of the epic presented by N. Akhmetbekov is the original text recorded from storytellers across the country, while later revised versions contain poetic and artistic edits. In addition, the article defines the place of the love epic within the genre, its historical basis, and formulates the importance of introducing the manuscript heritage into scientific circulation.